Cross‐sectional study of patient‐reported neurobehavioral problems following hematopoietic stem cell transplant and health‐related quality of life. Issue 12 (21st May 2014) - Wu, Lisa M.; Austin, Jane; Valdimarsdottir, Heiddis; Isola, Luis; Rowley, Scott D.; Diefenbach, Michael A.; Cammarata, Meredith; Redd, William H.; Rini, Christine
Abstract Objective Although hematopoietic stem cell transplant (HSCT) patients may experience neurocognitive impairment, experiences of neurobehavioral problems (including apathy and disinhibition) are understudied. These experiences reflect behavioral signs and symptoms of neurological dysfunction that can potentially reduce health‐related quality of life (HRQOL). Understanding them is important because they may be confused with other diagnoses, including depression, potentially leading to inappropriate treatments. The objectives of this preliminary cross‐sectional study were to describe HSCT patients' neurobehavioral functioning pre‐HSCT and post‐HSCT and to examine relations with HRQOL. Methods Patients (n = 42) 9 months to 3 years post‐HSCT completed measures of neurobehavioral functioning to report apathy and disinhibition pre‐HSCT (retrospectively) and post‐HSCT (currently). Paired t‐tests and McNemar tests were used to explore differences in the incidence of patient‐reported neurobehavioral problems within and across time points. Regression analyses were conducted to examine relations between neurobehavioral functioning and physical and mental HRQOL. Results Elevated levels of apathy were reported by many patients post‐HSCT (36%) and increased significantly from pre‐HSCT to post‐HSCT (p = 0.001). Hierarchical regression analysis indicated that higher levels of apathy were associated with reduced mental HRQOL (p < 0.05) even after controlling for depressed mood and fatigue. Conclusions Findings from this preliminary study highlight the importance of investigating neurobehavioral problems, particularly apathy, in HSCT patients. Because apathy is often confused with other diagnoses and may worsen HRQOL, understanding the nature of these symptoms has implications for interventions. Further research is needed in this important area. Copyright © 2014 John Wiley & Sons, Ltd.